Types of Paragraph Writing in the International Journals - Adi Sutrisno (Universitas Ahmad Dahlan, 2019)
The patterns of paragraph writing as commonly used in the international journal are deemed necessary to be studied by scholars of non-English background wishing to write an article for publication in the international journals. Scholars of non-English speaking background, according to a number of research reports on rhetoric contrastive, have a somewhat different approach in their paragraph composition. This difference might create difficulties for the scholars to swing their type of paragraph writing to the one which does not belong to them. Therefore, it is imperative that the scholars of non-English speaking background study the writing convention as commonly used in the international journal. This study sought to identify the patterns of paragraph writing that is commonly used in international journals. For the purpose of this study, a total of 250 paragraphs of the 25 international journal articles were selected for analysis whether the pattern of paragraph is more oriented to deductive or inductive one. Analyses were performed by two raters assisted by a native speaker of English. The results showed that more than 86% paragragh patterns were written using deductive pattern, while the rest, about 11% used inductive pattern, and the remaining 2% used a sandwich pattern.